THE ROLE OF POLICY INTERVENTIONS IN INFLATION TARGETING: A SOUTH ASIAN PERSPECTIVE DURING COVID-19 - P, Rabanal; Quint, D (Economics and Statistics Research Journal (ESRJ), 2023)
This study analyzes the impact of COVID-19 policy actions on inflation targeting in South Asian countries. Using monthly data collected from March 2020 to May 2021, the study examines the impact of various policies, including monetary and fiscal measures, grants and aids, direct credit support, and healthcare targeted policies, on the Consumer Price Index (CPI) in five South Asian Association of Regional Cooperation (SAARC) member countries (Bangladesh, India, Nepal, Pakistan, and Sri Lanka). The study finds that monetary policy and financial actions had a significant negative impact on CPI, while fiscal measures and grants/aid were inconclusive. Direct credit support and healthcare targeted policies had a significant impact on CPI in the SAARC countries considered. The study suggests that credit support measures provided support in curbing rising inflation, while healthcare support measures had a significant impact on lowering CPI. This study contributes to the literature on the impact of COVID-19 on financial and economic systems in Asian countries by providing evidence on the efficacy of policies that evolved in response to the pandemic. The findings of this study have important implications for policymakers in understanding the relative importance of different types of policies in stabilizing CPI and maintaining price stability